Energy Audit and Assessment of Energy Saving Opportunities Using Analytical Hierarchy Process in Public Health Center Buildings in Jakarta to Optimize Energy Efficiency - Monika, Ratih; Garniwa, Iwa (Institut Teknologi Bisnis AAS Indonesia, 2025)
The Government of Indonesia has issued a regulation through Government Regulation No. 33 of 2023, mandating central and regional governments to implement energy conversion efforts. Conducting energy audits in public health center buildings in Jakarta has become an essential step toward realizing concrete energy conservation actions. This study was conducted at the XYZ District Public Health Center with the objectives of assessing energy consumption patterns, identifying potential energy-saving opportunities, and determining the prioritized recommendations to optimize energy efficiency. The audit findings indicate that the building still holds an energy-saving potential of 54.66%, with an estimated annual saving of 146,204.95 kWh or approximately IDR 139,625,731. If energy-saving strategies are applied on a broader scale, Jakarta's potential energy savings could reach 0.43%, or about 6,433,017.8 kWh/year, equivalent to IDR 1,030,598,693/year. At the national level, potential energy savings could reach 19.5%, amounting to 1,030,598,692.55 kWh/year or IDR 984,221,777,819/year. To assist public health center management in determining the prioritization of energy-saving opportunities, this study employed the Analytical Hierarchy Process (AHP) method using 4 criteria and 8 alternatives based on the energy audit recommendations. Expert assessments involving representatives from the health center, government, and practitioners determined that the priority order for the criteria level: ease of implementation, implementation cost, impact on service, and energy-saving potential. Meanwhile, the prioritized alternatives level: AC temperature setting, socket management, reduction in AC infiltration load, lighting operation management, AC operation management, AC maintenance, application of motion sensor technology, and replacement of energy efficient air conditioning technology.